Pengukuran Konduktifitas Termal pada Bahan Kayu, Kapur, dan Besi - Annas, Muhamad Azwar; Chasanah, Uswatun; Sandi, Aris (Lembaga Yasin AlSys, 2023)
Measurement Of Thermal Conductivity In Wood, Lime And Iron have been carried out with the aim of determining the termal conductivity of a material and knowing the factors that affect the termal conductivity of a material. The tools and materials in this experiment were two metal cylinder conductors, the test material (in the form of a cylinder) in the form of cotton wool, iron and wood, an electric stove, a pyrometer, water, clamps and a stopwatch with the stove working steps turned on, piling up the test material placed in the middle of the metal conductor, heated for 10 minutes, the temperature was measured with a pyrometer on the bottom surface, the metal surface below the test material, the metal surface above the test material, and the top surface. Note, the test material and metal conductors are cooled with water and repeated for the other test materials. The working principle used is termal convection termal conduction, temperature measurement. The results of the experiment showed that the value of the termal conductivity was 27.13 W/m°C for wood, 18.6 W/m°C for lime, and 60.6 W/m°C for iron. As for the conductivity is influenced by the temperature difference of each surface of the material, the type of material, the cross-sectional area.